The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/ijms23073528
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoplasmic Reticulum Stress and NLRP3 Inflammasome in Liver Disorders

Abstract: The endoplasmic reticulum (ER) is a key organelle responsible for the synthesis, modification, folding and assembly of proteins; calcium storage; and lipid synthesis. When ER homeostatic balance is disrupted by a variety of physiological and pathological factors—such as glucose deficiency, environmental toxins, Ca2+ level changes, etc.—ER stress can be induced. Abnormal ER stress can be involved in many diseases. NOD-like receptor family pyrin domain-containing 3 (NLRP3), an intracellular receptor, can perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…Its functions include protein synthesis and folding, assembly, and transportation, and it is also the principal place for calcium storage, intracellular lipid metabolism, and steroid hormone synthesis. However, when ER homeostasis is disrupted by physiological or pathological factors, unfolded or misfolded proteins accumulate in the ER, and ER function is impaired, resulting in ERS . To restore this damage, the unfolded protein (UPR) response is activated.…”
Section: Discussionmentioning
confidence: 99%
“…Its functions include protein synthesis and folding, assembly, and transportation, and it is also the principal place for calcium storage, intracellular lipid metabolism, and steroid hormone synthesis. However, when ER homeostasis is disrupted by physiological or pathological factors, unfolded or misfolded proteins accumulate in the ER, and ER function is impaired, resulting in ERS . To restore this damage, the unfolded protein (UPR) response is activated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, FXR agonists inhibit the triggering of nod-like receptor pyrin 3 (NLRP3) inflammasome, which is included in the overstated immune response and propagation of hypercytokinemia in severe SARS-CoV-2 infection (Batiha et al 2021 ; Lu et al 2022 ). In this sense, OCA via provoking of FXRs may lessen the risk of hyperinflammation and production of hypercytokinemia, in patients with severe Covid-19.…”
Section: The Possible Mechanisms Of Oca In Covid-19mentioning
confidence: 99%
“…The innate immune reaction and inflammation could be regulated by SHP through supressing the expression of TLR4, NLRP3 inflammasome, and NF-κB (Yuk et al 2016 , 2011 ). Notably, TLR4, NLRP3 inflammasome, and NF-κB are highly stimulated in SARS-CoV-2 infection resulting in hyper-inflammation and hypercytokinemia, (Batiha et al 2021 ; Lu et al 2022 ). SHP affords a negative regulatory effect on various signaling pathways.…”
Section: Fxr and Signaling Pathways In Covid-19mentioning
confidence: 99%
“…Activation of inflammasomes leads to augmentation of caspases, resulting in apoptosis, pyroptosis, release of proinflammatory cytokine interleukin-1β (IL-1β) and interleukin-18 (IL-18) ( 17 ). The NLRP3 inflammasome which comprises NOD-like receptor family pyrin domain-containing 3 (NLRP3), apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC) and caspase-1 cooperates with ER stress and mitochondria damage in the pathogenesis of many liver disorders such as ASH, NAFLD, nonalcoholic steatohepatitis (NASH), hepatic ischemic injury, and hepatotoxicity ( 18 , 19 ). Moreover, experimental research has demonstrated that deubiquitination and activation of NLRP3 inflammasome facilitates HCV life cycle in HCV-infected hepatic cells ( 20 ) and HBV X antigen activates NLRP3 inflammasome under oxidative stress and advances pyroptosis in hepatic cells ( 21 ).…”
Section: The Role Of Inflammation In Hepatocarcinogenesismentioning
confidence: 99%